DURAL TEAR: A FEARED COMPLICATION IN LUMBAR SPINE SURGERY - Sohail Amir; Bilal Khan; Aurangzeb; Khaleeq-Uz-Zaman (Journal of University Medical & Dental College, 2019)
ABSTRACT: OBJECTIVE: The objective of this study is to determine the incidence of dural tear in lumbar spine surgeries and associated risk factors. MATERIAL AND METHODS: In this descriptive cross sectional study, 117 Patients were studied in the department of Neurosurgery, Naseer Teaching Hospital Peshawar from February 2013 to December 2016. All patients with either gender or age who needed spinal surgery for lumbar disc disease, spinal stenosis, and re-do surgery were included in study while those with trauma, tumor and infection were excluded. Data was collected regarding the age of patients, co-morbid conditions, lumbar spine disease, level of involvement, type of operation, occurrence of dural tear, site of dural tear and complications were recorded on a predesigned proforma. Data was analyzed using SPSS version 20.0. RESULTS: Out of 117 patients 63(53.8%) were male and 54(46.1%) were female. Male to female ratio was 1.2:1. In our study the age of patient ranged from 16 to 80 years with mean age 38 + 2.34 years Dural tear occurred in 15(12.8%) of patients, among these 5 (4.2%) dural tear in lumbar disc prolapsed , 8(6.8%) in spinal stenosis and 2 (1.7%) in surgery for recurrent disc disease. The complication rate was 19(16.2%), among these the most common complication was cerebrospinal ﬂuid leak (CSF) in 7(5.9%), delayed wound healing in 5(4.2%), discitis in 4(3.4%) and others in 3(2.5%) of patients. CONCLUSION: Dural tear (DT) is not uncommon complication during spinal surgery and represent a serious challenge for both surgeon and patients. Female, obese, older age, re-do surgery are the major risk factor for dural tear.